(untitled) (Semiárida, 2020)
The main purpose of this study was to identify resistance of experimental lines of Bromus catharticus, B. parodii y B. brevis to Ustilago bullata, an important head smut pathogen of brome grass. Seeds of 100 experimental lines were inoculated with a uniform mass of ustilospores obtained from each species and seeded in field plots in 1992. At maturity the number of smutted panicles were counted. Data were compared by using "1.2 test of homogeneity. B. brevis and B. parodii experimental lines varied in their reactions to U. bullata. AII B. catharticus plants were susceptible to the pathogen. Differences in susceptibility were found between geographic sources of B. brevis and B. parodii genotypes.